Penggunaan Teknologi dalam Pembelajaran Seni Gerak dan Tari Anak Usia 5-6 Tahun di RA Bunayya 2 - Febby Ardera Boru Ginting; Mivtahul Zannah; Mutiara Firdausi An Tasya; Najwa Mawaddah; Hilda Zahra Lubis (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
The rapid development of digital technology has brought significant changes to the field of education, including movement and dance learning for early childhood. In the context of Early Childhood Education (ECE), technology integration has been proven to enhance engagement, creativity, and cognitive development in children aged 5-6 years. This study aims to examine the extent of technology use in dance learning at RA Bunayya 2. Using a descriptive qualitative approach, data were collected through observations and interviews with educators. The research findings indicate that technological tools such as projectors and digital screens enhance children's focus, participation, and creativity in dance activities. Additionally, various supporting technologies, including mobile phones, cameras, microphones, and projectors, are utilized to enrich the learning experience, making the educational process more interactive and engaging. However, challenges such as unstable internet connections and varying levels of concentration among children require careful implementation. This study highlights the importance of balancing technology use in ECE, ensuring that digital tools serve as a support rather than replacing conventional pedagogical approaches.